Functional study of waist-hip ratio associated loci and the WARS2 gene as modulators of fat distribution. - Muso, M (2019)
Waist-hip ratio (WHR) is a risk factor for diabetes and cardiovascular disease. Genome-wide association studies identified 346 loci linked to increased WHR adjusted for Body Mass Index (WHRadjBMI) (Shungin et al., 2015; Pulit et al., 2018). To elucidate the genetic underpinning of WHRadjBMI, I aimed to identify causal SNPs in 4 of these loci and test the tryptophanyl-tRNA synthetase 2 (WARS2) gene, previously shown to severely affect adipose mass, as modulators of fat distribution and browning.